The Contribution Of Environmental Accounting And Green Economy In Supporting The Increase In Income Of Madirsan Ornamental Plant Msmes In Deli Serdang Regency - Hasanah, Nurul; Tambunan, Sari Bulan; Siregar, Muhammad Akbar; Lubis, Adelina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy, including the ornamental plant subsector in Deli Serdang Regency, which is growing in line with the green lifestyle trend. This study analyzes the influence of environmental accounting and green economy on the revenue of the Madirsan Ornamental Plant MSME using quantitative methods, using 50 respondents through a Likert questionnaire and multiple linear regression analysis. The results show that both variables have a significant positive effect on increasing revenue, with green economy as the dominant factor. The R² value of 0.643 indicates that 64.3% of the variation in revenue is explained by both variables, the remainder is influenced by other factors. It is concluded that the implementation of environmental accounting and green economy increases the competitiveness, efficiency, and sustainability of MSMEs while supporting sustainable economic development.